STRATEGI MANAJEMEN PENDIDIKAN ISLAM DALAM MENCIPTAKAN MADRASAH MENYENANGKAN SEBAGAI RUANG BELAJAR YANG EDUKATIF DAN BERORIENTASI PADA KARAKTER - Fatikhasari, Viona Hernanda; Diansyah, Hamdan Nur; Syafi’udin, Syafi’udin; Khauroh, Nazilatul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Creating the best learning environment for student academic success is a challenge for Islamic education. Students' learning and personal growth, both personal and academic, are crucial. To create an instructive, inspiring learning environment focused on the development of noble morals in accordance with Islamic law, this madrasah utilizes contemporary creative concepts to create an enlightening, inspiring learning environment centered on teaching moral behavior in accordance with Islamic law. Islamic education management strategies for creating a fun madrasah include holistic curriculum management that integrates active and varied learning, conducive physical environment management, teacher competency development, and the establishment of a positive work culture. Character building programs are implemented through role models, daily habits, and values-based learning integrated into all madrasah activities. Parental and community involvement is optimized through intensive communication and strategic partnerships. The implementation of an authentic evaluation system, the use of learning technology aligned with Islamic values, and the development of extracurricular programs based on interests and talents are essential supporting components. A continuous monitoring and evaluation system ensures continuous improvement in the quality of education